2003
DOI: 10.1021/bi027434m
|View full text |Cite
|
Sign up to set email alerts
|

Sulfenic Acid Formation in Human Serum Albumin by Hydrogen Peroxide and Peroxynitrite

Abstract: Human serum albumin (HSA), the most abundant protein in plasma, has been proposed to have an antioxidant role. The main feature responsible for this property is its only thiol, Cys34, which comprises ∼80% of the total free thiols in plasma and reacts preferentially with reactive oxygen and nitrogen species. Herein, we show that the thiol in HSA reacted with hydrogen peroxide with a second-order rate constant of 2.26 M-1 s-1 at pH 7.4 and 37 °C and a 1:1 stoichiometry. The formation of intermolecular disulfide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
223
0
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(241 citation statements)
references
References 47 publications
9
223
0
9
Order By: Relevance
“…5). Under conditions of excess enzyme, the stoichiometry of the reaction was two thiols oxidized by each peroxynitrite added, consistent with the reported stoichiometry for direct thiol oxidation, which involves a two-electron oxidation of the thiol to its sulfenic derivative, an intermediate detected in the case of peroxynitrite-mediated oxidation of the single thiol group of human serum albumin (54). Peroxynitrite-derived radicals CO 3 .…”
Section: Discussionsupporting
confidence: 82%
“…5). Under conditions of excess enzyme, the stoichiometry of the reaction was two thiols oxidized by each peroxynitrite added, consistent with the reported stoichiometry for direct thiol oxidation, which involves a two-electron oxidation of the thiol to its sulfenic derivative, an intermediate detected in the case of peroxynitrite-mediated oxidation of the single thiol group of human serum albumin (54). Peroxynitrite-derived radicals CO 3 .…”
Section: Discussionsupporting
confidence: 82%
“…Thus, dimedone (5,5-dimethyl-1,3-cyclohexanedione) selectively derivatizes sulfenic acid yielding a stable thiother, which can be identified by mass spectrometry or by incorporation of a radioactive, fluorescent or biotin tag (41,48). In the case of albumin, the mass spectrometric detection of dimedonetrapped sulfenic acid confirmed that the modification occurred at Cys34 (12).…”
Section: Detection Of Sulfenic Acid In Human Serum Albuminmentioning
confidence: 93%
“…The albumin thiol reacts with hydrogen peroxide (H 2 O 2 ) and peroxynitrite (ONOO -) with rate constants of 2.2-2.7 and 3.8 x 10 3 M -1 s -1 , respectively, at pH 7.4 and 37°C (11)(12)(13). These values are similar to free cysteine and glutathione.…”
Section: Reactivity Of the Albumin Thiolmentioning
confidence: 94%
“…Titration data were fitted to the Nernst equation using nonlinear regression. The n value was set to 2 as the disulfide-dithiol exchange, and the oxidation and reduction of Cys sulfenic acid are expected to be two-electron transfer processes (35)(36)(37)(38). The redox potential is reported as the mean value Ϯ S.D.…”
Section: Methodsmentioning
confidence: 99%